A imunidade tributária de fundo de previdência mantido por instituição filantrópica de educação e a necessidade de governança corporativo-previdenciária - Neves, Julio Cesar das (2016)
The present dissertation sought to present fairly straightforward doctrinal and jurisprudential debate about the tax immunity of private pension fund, maintained by philanthropic institution of education, nonprofit – for their employees. Where, initially, it was social solidarity, as constitutional basis to ensure a fair and egalitarian society. Then sought to introduce demographic scenario social security raised by the Brazilian Institute of geography and statistics-IBGE. Furthermore, it was held about explanation of constitutional power to tax immunities – emphasizing the constitutional and legislation infra-constitutional commandment that surround and permeate the pension funds. There was talk the sponsorship of private pension plans by Entity, non-profit education in favor of their employers. Already at the end were presented needs to have a corporate and social security governance of pension plans. And, in conclusion found that observing the commandments law, pension funds are effectively supported by the standard vaccines and lend themselves to an important role with regard to the political-administrative and social balance of the country.